If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(3x + -1) = 3(12x + 6) Reorder the terms: 12(-1 + 3x) = 3(12x + 6) (-1 * 12 + 3x * 12) = 3(12x + 6) (-12 + 36x) = 3(12x + 6) Reorder the terms: -12 + 36x = 3(6 + 12x) -12 + 36x = (6 * 3 + 12x * 3) -12 + 36x = (18 + 36x) Add '-36x' to each side of the equation. -12 + 36x + -36x = 18 + 36x + -36x Combine like terms: 36x + -36x = 0 -12 + 0 = 18 + 36x + -36x -12 = 18 + 36x + -36x Combine like terms: 36x + -36x = 0 -12 = 18 + 0 -12 = 18 Solving -12 = 18 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6+3r-3=8r+11-4r | | 4(7-2)= | | log(4x)+log(9x)=2 | | 4x-2(x-1)+5= | | 2r^3+14r^2-36r=0 | | 2x-5*(x+3*(3-x))= | | 7x-12-12x= | | 5(x-6)=55/11 | | -12.4=19.1+n/-7.9 | | n+3n+4n=100 | | 2w+2(w+10)=28 | | x+4x=258 | | 5640/9.4 | | 18p-45=o | | In(x+2)+in(x-2)=7 | | 3x+x=360 | | In(x)+in(x+1)=2 | | In(x)+in(x+1)=12 | | 9(x+9)=134 | | 1/4+5/12 | | 4n^2=6 | | 3/5x-5=-2/5x+7 | | 8q=18-2p | | 4x+2=4x+5 | | 12e-4+e+18-2e= | | 63-2x=34x+19 | | 26a+5+2b-4a-15b= | | 2x-1/2=x+7/4 | | ((-w+3)/2)=2 | | 2x+3x=28-2x | | -5p^7+12p^4+10-6p^4-1+13p^7= | | -10-7x=11 |